2021
DOI: 10.3390/en14040895
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Improvement of Photovoltaic Modules via Back Surface Cooling

Abstract: Crystalline silicon photovoltaics are a cardinal and well-consolidated technology for the achievement of energy efficiency goals, being installed worldwide for the production of clean electrical energy. However, their performance is strongly penalized by the thermal drift, mostly in periods of high solar radiation where solar cells reach considerably high temperatures. To limit this aspect, the employment of cooling systems appears a promising and viable solution. For this purpose, four different cooling syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…Their results are expected since this is an immersion. Bevilacqua et al [38] showed through their study that a simple spray cooling mechanism on a PV module could increase the electrical efficiency up to 1.6%. In a study by Abdolzadeh and Ameri [39] they used water spraying on the PV module's front surface to increase the cell efficiency by 3.26%.…”
Section: Electrical Analysis Of Both Panelsmentioning
confidence: 99%
“…Their results are expected since this is an immersion. Bevilacqua et al [38] showed through their study that a simple spray cooling mechanism on a PV module could increase the electrical efficiency up to 1.6%. In a study by Abdolzadeh and Ameri [39] they used water spraying on the PV module's front surface to increase the cell efficiency by 3.26%.…”
Section: Electrical Analysis Of Both Panelsmentioning
confidence: 99%
“…Experimental tests and numerical analyses on monocrystalline or polycrystalline photovoltaic panels show that the decrease in efficiency, as the operating temperature increases, and the necessity of cooling solutions are current concerns in the literature [11][12][13]16,30,31].…”
Section: Related Researchmentioning
confidence: 99%
“…These factors may very well affect the efficiency and the profitability of PVs. For instance, several studies have discussed the negative effects of elevated temperatures on PV modules and suggested different methods of improving their efficiencies [11][12][13]. Other studies have investigated the effect of dust on PV modules [14,15].…”
Section: Introductionmentioning
confidence: 99%